Reconstruction of Criminal Law Policy for Children From a Restorative Justice Perspective in Indonesia - Aurel Rica Utami, Agel; Zarzani, T. Riza; Rafianti, Fitri (International Conference Epicentrum of Economic Global Framework, 2025)
Based on Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, the concept of restorative justice is adopted, which is realized through diversion efforts. Restorative Justice is a model for resolving criminal cases that prioritizes the restoration of victims, perpetrators, and the community. The goal of restorative justice is the participation of victims and perpetrators, the participation of citizens as facilitators in resolving cases, so that there is a guarantee that children or perpetrators will no longer disrupt the harmony that has been created in society. This study aims to analyze the policy of juvenile criminal law and how restorative justice works. This study uses normative research types and secondary data sources as well as legislative approaches and case approaches. Based on the results of the study, the criminal law policy towards children as perpetrators of crimes in Indonesia is specifically regulated through Law No. 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA). This regulation aims to provide special protection, guarantee the future of children, and prioritize a restorative justice approach (recovery) over retaliation. Restorative justice for children in conflict with the law is the resolution of criminal cases that emphasizes restoration to the original state rather than retaliation. This approach must be prioritized in the justice system to restore social balance and avoid negative impacts or stigma on the future of children. Reconstruction of child criminal law policy in Indonesia is crucial to shift the paradigm from retributive to restorative. This approach focuses on resolving cases involving victims, perpetrators, families, and the community to achieve dialogue, responsibility, and peace.